Initial Development of Lamota (Salicornia europae) Yogurt As a Functional Drink - Munandar, Imam; Sari, Ratna Nurmalita; Suriyadin, Adi; Havied, Arif Rahman (Journal of Aquaculture and Fish Health, 2024)
Salicornia europae is a marine plant that grows   in coastal areas and tides. In Sumbawa, this plant lives in the former area of ponds and usually called as lamota.  S. europae contains beneficial ingredients such as iodine, minerals, vitamins, antioxidants, unsaturated fatty acids, and sugars.  Marine plant innovations in S.  Europae, which is rich in iodine into processed yogurt, has not been well explored.  This study aimed to develop the processing of lamota into functional yogurt drink. Complete Randomized Design (CRD) was used in this experiment with a single factor of 6 levels of lamota concentration. Iodine content, ash content, pH and scoring test were carried out to find out the best quality of the lamota yogurt. The results showed that the iodine content of the product was 29.01 mcg / g dry weight and ash content was 10.59%. The pH showed that the addition of lamota minimally affected the pH of the yoghurt. In the organoleptic test found that 25% addition of lamota extract was the most preferrable concentration compared to 5, 10, 15, and 20% based on the color, taste, texture, aroma. Panelist describe the 25% lamota addition has greenish color, a little bit salty, watery texture, and green aroma. Based on the iodine content and the best consumers acceptance the yogurt with 25% addition of lamota could be categorized as a rich in iodine drink and a promising product to improve the functional characteristics of yogurt as well develop a value added local marine commodity with unique flavor.